PEMBERDAYAAN EKONOMI MASYARAKAT RT 05 RW IX KELURAHAN KROBOKAN KECAMATAN SEMARANG BARAT MELALUI PENGOLAHAN BAHAN PANGAN LOKAL DAN PEMASARANNYA - Mei Sulistyoningsih; Reni Rakhmawati; Dwi Prastiyo Hadi; Iffah Muflihati; Umar Hafidz Asy?óÔé¼Ôäóari Hasbullah (Universitas PGRI Semarang, 2015)
Abstract ?é?á The purpose of this activity is to increase of people?óÔé¼Ôäós income through local food processing and its marketing by empowerment of communities. Participants of these activities include member of RT 05 RW IX, Kelurahan Krobokan, sub-district of West Semarang, Semarang City. The method are discussion, practice, and simulation. Implementation of activities is to encourage community to be entrepreneurs in increasing family incomes not only just relying on the income from the work as laborers or workers. Training activities of local food into a healthy diet has a positive response from family group in RT 05 RW IX, Kelurahan Krobokan, sub-district of West Semarang, Semarang City. ?é?á Keywords : family income, local food, entrepreneur, marketing